Analysis of changes in the education system in contemporary societies on the example of Poland and Finland - Ewelina Anna Kurowicka (Kazimierz Wielki University, 2020)
Education is an important field that is the basis for functioning in a modern society. For this reason, there is a need for all activities related to the organization of the teaching process to be carried out in an effective way that will create optimal conditions for teachers to transfer their knowledge to students. It is important to create an education system that will respond to the current challenges in the field of teaching and educating a young person. One of the most important factors determining the proper course of the education process is the appropriate preparation of the teaching staff. In this publication, the basic concepts related to education and the educational system will be discussed. The aim of this article is to analyze the changes in the education system on the example of Poland and Finland.